Tropomyosin‐related kinase C (TrkC) enhances podocyte migration by ERK‐mediated WAVE2 activation. Issue 3 (3rd January 2018) - Gromnitza, Sascha; Lepa, Carolin; Weide, Thomas; Schwab, Albrecht; Pavenstädt, Hermann; George, Britta
Abstract : Podocyte malfunction is central to glomerular diseases and is marked by defective podocyte intercellular junctions and actin cytoskeletal dynamics. Podocytes share many morphologic features with neurons, so that similar sets of proteins appear to regulate cell process formation. One such protein is the tropomyosin‐related kinase C (TrkC). TrkC deficiency in mice leads to proteinuria as a surrogate of defective kidney filter function. Activation of endogenous TrkC by its ligand neurotrophin‐3 resulted in increased podocyte migration—a surrogate of podocyte actin dynamics in vivo . Employing a mutagenesis approach, we found that the Src homologous and collagen‐like (Shc) binding site Tyr 516 within the TrkC cytoplasmic domain was necessary for TrkC‐induced migration of podocytes. TrkC activation led to a mobility shift of Wiskott‐Aldrich syndrome family verprolin‐homologous protein (WAVE)‐2 which is known to orchestrate Arp2/3 activation and actin polymerization. Chemical inactivation of Erk or mutagenesis of 2 of 4 known Erk target sites within WAVE2, Thr 346 and Ser 351, abolished the TrkC‐induced WAVE2 mobility shift. Knockdown of WAVE2 by shRNA abolished TrkC‐induced podocyte migration. In sum‐mary, TrkC signals to the podocyte actin cytoskeleton to induce migration by phosphorylating WAVE2 Erk de‐pendently. This signaling mechanism may be important for TrkC‐mediated cytoskeletal dynamics in podocyte disease.—Gromnitza, S., Lepa, C., Weide, T., Schwab, A., Pavenst ädt, H., George, B. Tropomyosin‐related kinase C (TrkC) enhances podocyte migration by ERK‐mediated WAVE2 activation. FASEB J. 32, 1665‐1676 (2018). www.fasebj.org